Altitudinal distribution of aquatic macroinvertebrates and its relation to environmental variables in an Amazon river system (Perú) - Arana-Maestre, Jerry (2021)
In the Peruvian Amazon, there are few ecological studies on the diversity patterns of aquatic macroinvertebrates, essential for the management of these fluvial ecosystems. In such context, our objective was to determine the taxonomic composition and its relationship with environmental variables along an altitude gradient of the Alto Madre de Dios River, a basin with the potential to register new species. We established 22 stations in an altitudinal range from 398 to 2411 masl and evaluated the water physicochemical characteristics and the fluvial habitat: pH, water temperature (T, ° C), electrical conductivity (CE, μS.cm-1), river width (A, m), depth (P, cm), shadow, current flow speed (m · s-1), and depth. We took macroinvertebrate samples with a 200-μm-mesh-size kick net and identified 56 taxa distributed in the orders Acari, Ephemeroptera, Coleoptera, Diptera, Hemiptera, Megaloptera, Odonata, Plecoptera, Trichoptera, and Decapoda. In the multivariate classification and grouping analysis, four groups of statistically differentiated stations (p <0,05) were classified, mainly by speed and the type of dominant substrate, which explains the abundance and wide distribution of Chironomidae, Baetodes, Traulodes, and Anacroneuria. Macroinvertebrate taxa changed notably along the gradient reporting a greater diversity in areas with middle altitudes and a relationship with environmental variables.